2012
DOI: 10.1177/1040638712440991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different embryonating bird eggs and cell cultures for isolation efficiency of avian Influenza A Virus and Avian paramyxovirus serotype 1 from real-time reverse transcription polymerase chain reaction–positive wild bird surveillance samples

Abstract: Virus isolation rates for influenza A virus (FLUAV) and Avian paramyxovirus serotype 1 (APMV-1) from wild bird surveillance samples are lower than molecular detection rates for the specific viral genomes. The current study was conducted to examine the possibility of increased virus isolation rates from real-time reverse transcription polymerase chain reaction (real-time RT-PCR) using alternative virus isolation substrates such as embryonating duck eggs (EDEs), embryonating turkey eggs (ETEs), Madin–Darby canin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Matrix Ct values are inversely related to the amount of viral RNA present in a sample-samples with low CT values have more viral RNA while samples with less RNA must undergo additional cycles to reach the threshold response. Although the maximum limit of detection for the matrix PCR assay is 45, many studies have shown that virus isolation success is much higher for samples having lower (<35) Ct counts [7,9,13]. In the present study, viruses were isolated from 39% of birds indicating that these birds were shedding infectious virus (Figure 1 and Table 1).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Matrix Ct values are inversely related to the amount of viral RNA present in a sample-samples with low CT values have more viral RNA while samples with less RNA must undergo additional cycles to reach the threshold response. Although the maximum limit of detection for the matrix PCR assay is 45, many studies have shown that virus isolation success is much higher for samples having lower (<35) Ct counts [7,9,13]. In the present study, viruses were isolated from 39% of birds indicating that these birds were shedding infectious virus (Figure 1 and Table 1).…”
Section: Discussionmentioning
confidence: 48%
“…Eight VTM samples with Ct values >35 grew in eggs, including two with values above detectable limits (>45), while three samples with Ct values <35 did not grow. Thus, as shown in previous studies [5,9,10,11,12,13] the VTM matrix Ct value is a good, but imperfect predictor for virus growth in ECE, and several isolates would have been missed if a low matrix Ct value were used as a prerequisite for inoculation into eggs. …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The majority of samples had cycle threshold ( C t ) values around 37–39, whereas isolation is ideally achieved at or below a cycle threshold value of 33. 25,26,27 …”
Section: Resultsmentioning
confidence: 99%